Role of myeloid growth factors in chemotherapy induced neutropenia - Bharadwaj, Ravinutala Srinath; Aruna, Donepudi (International Journal of Basic & Clinical Pharmacology, 2017)
Neutropenia is a major dose limiting toxicity of many chemo therapeutic regimens. Haemopoietic colony - stimulating factors (CSFs) have been shown to reduce the duration and severity of chemotherapy induced neutropenia (CIN) and risk of febrile neutropenia. Supportive care with myeloid growth factors improve chemotherapy delivery by minimizing chemotherapy dose reductions or treatment delays by enabling the delivery of full dose chemotherapy (dose dense) in short time intervals. The goal of this article is to give comprehensive review of current literature regarding medical practice guidelines and risk assessment models for appropriate use of myeloid growth factors and management of febrile neutropenia.